A Review of Employee Turnover from the Perspective of the Philosophy of Science - Sudrajat, Jajat; Siow, Hong Loke; Permana, Ibar Adi (Indo Consultan Energi, 2024)
Turnover is a phenomenon that commonly occurs in an organization, especially companies. The research results show that from the perspective of philosophical knowledge, turnover can be explained in three dimensions: ontology, epistemology, and axiology. In the ontological dimension, turnover includes the true meaning of turnover science, which can be proven to exist in every organization. The epistemological dimension of turnover science is related to the basis of knowledge, sources, characteristics, the truth of knowledge, and how to obtain turnover knowledge. Finally, in the axiological dimension, the discussion of turnover includes the relationship between knowledge and values, namely the feasibility of turnover science to be developed and the function and usefulness of turnover science. In the end, turnover science needs to be developed so that its benefits can be felt more, especially in anticipating how to ensure that the turnover phenomenon only occurs occasionally in companies, even though this is inevitable due to various situations and conditions in the organization.